THE EFFECT OF AMBASSADOR BRAND AND HEDONIC SHOPPING ON IMPULSE BUYING OF SHOPEE PPLICATIONS IN HIGH SCHOOL OF ECONOMICS AND INTEGRATED - Muhammad Najih; Alfi Amaliya (Proceeding International Seminar of Islamic Studies, 2022)
The development of new technology today has reached all circles of the general public and businesses in Indonesia where these developments affect the existing market conditions. Existing business actors must be ready to respond to any new technological developments where each development cannot be separated from the internet as a fulfillment of needs. The use of the internet in Indonesia as a digital marketing communication medium, namely buying and selling online or what we usually call e-commerce is growing rapidly until now, one of which is Shopee. Shopee is an e-commerce (online buying and selling) based on mobile applications, which is developing in Indonesia. The current development of the shopee application has resulted in impulse buying among the public, especially students. Factors that make someone impulse buying are brand ambassadors and hedonic shopping. The purpose of this study was to analyze the effect of brand ambassadors and hedonic shopping on impulse buying. This research was conducted at STEBIS AL-Ulum. This research is a quantitative research with the number of respondents is 70 students. The results of this study indicate that there is a positive and significant influence of brand ambassadors and hedonic shopping partially or simultaneously on impulse buying. Meanwhile, brand ambassadors and hedonic shopping can explain impulse buying by 75.2%, the remaining 24.8 is influenced by other factors.